Metaverse and Education: A New Period is Beginning - Yildirim, Pelin; Keçeci, Gonca (T.C. Milli Egitim Bakanligi, 2024)
Within the scope of the measures taken in the COVID-19 pandemic crisis, which has affected the entire world, face-to-face events have been moved to digital platforms. Throughout global pandemic, many countries applied various distance education applications compatible to their technological infrastructure and resources to cope with disruption in education. In this process, online education has swiftly been substituted for face-to-face education to ensure learning continuity. Since this rapid transition, learning methods using digital technologies in education and training have started to attract more attention. One of the most important examples of digital transformation in education is the metaverse technology which gained global attraction conceptually. Metaverse, derived from the words meta (after/beyond) and universe forming meta-universe, is a fictional universe that allows users to engage with three-dimensional virtual worlds using augmented reality and virtual reality technologies as well as personal mobile devices. This study explains what the metaverse is, investigates its reflections on education, provides sample metaverse projects and proposes further improvements. © (2024), (T.C. Milli Egitim Bakanligi). All rights reserved.
Metaverse ve Eğitim: Yeni Bir Dönem Başlıyor
Keywords: education; eğitim; metaverse; metaverse; society 5.0; toplum 5.0